2016
DOI: 10.1002/qua.25137
|View full text |Cite
|
Sign up to set email alerts
|

Periodic trends in constants of triatomic molecules

Abstract: Working from the arrangements of both row and group numbers developed within Mendeleev's periodic table of elements, periodic trends can be shown to exist in many constants of triatomic molecules: an extension of the Periodic Law for atoms to the realm of molecules. Trends are identified for vibrational frequencies, bond lengths, and to a lesser extent interior angles. This work includes empirical sources for such data, supplemented with calculations using diatomic analogs where possible. Otherwise, computatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
3

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
0
2
0
3
Order By: Relevance
“…8,25 multiplicidad del estado fundamental, los orbitales frontera, entre otras) relacionadas con los electrones de valencia de estas moléculas varían periódicamente con el número molecular N. Otras evidencias establecen que, las propiedades periódicas moleculares no sólo dependen del número de electrones de valencia, sino también del tamaño molecular, definido a groso modo como la suma de los períodos (en la tabla periódica de elementos) en los cuales se ubican los átomos constituyentes de la molécula. 28 En este sentido, Kong y Wu 28 y Barrow et al 14 han desarrollado estudios complementarios en esta área, ampliando la descripción computacional de más tendencias periódicas en moléculas triatómicas, cuyos trabajos apuntan a la identificación y caracterización de clusters, nanopartículas y especies químicas desconocidas, que puedan explicar la naturaleza del cosmos. 14,28 En las últimas décadas se ha evidenciado la discusión de algunas tendencias periódicas en materiales sólidos, con el objetivo de optimizar el desempeño de los materiales, mediante su modificación a nivel estructural.…”
Section: De La Periodicidad De Los Elementos a La Periodicidad De Losunclassified
See 2 more Smart Citations
“…8,25 multiplicidad del estado fundamental, los orbitales frontera, entre otras) relacionadas con los electrones de valencia de estas moléculas varían periódicamente con el número molecular N. Otras evidencias establecen que, las propiedades periódicas moleculares no sólo dependen del número de electrones de valencia, sino también del tamaño molecular, definido a groso modo como la suma de los períodos (en la tabla periódica de elementos) en los cuales se ubican los átomos constituyentes de la molécula. 28 En este sentido, Kong y Wu 28 y Barrow et al 14 han desarrollado estudios complementarios en esta área, ampliando la descripción computacional de más tendencias periódicas en moléculas triatómicas, cuyos trabajos apuntan a la identificación y caracterización de clusters, nanopartículas y especies químicas desconocidas, que puedan explicar la naturaleza del cosmos. 14,28 En las últimas décadas se ha evidenciado la discusión de algunas tendencias periódicas en materiales sólidos, con el objetivo de optimizar el desempeño de los materiales, mediante su modificación a nivel estructural.…”
Section: De La Periodicidad De Los Elementos a La Periodicidad De Losunclassified
“…28 En este sentido, Kong y Wu 28 y Barrow et al 14 han desarrollado estudios complementarios en esta área, ampliando la descripción computacional de más tendencias periódicas en moléculas triatómicas, cuyos trabajos apuntan a la identificación y caracterización de clusters, nanopartículas y especies químicas desconocidas, que puedan explicar la naturaleza del cosmos. 14,28 En las últimas décadas se ha evidenciado la discusión de algunas tendencias periódicas en materiales sólidos, con el objetivo de optimizar el desempeño de los materiales, mediante su modificación a nivel estructural. En la Figura 2 se representan esquemáticamente las aplicaciones de estas tendencias, discutidas a continuación.…”
Section: De La Periodicidad De Los Elementos a La Periodicidad De Losunclassified
See 1 more Smart Citation
“…Broader efforts to search for periodic laws for the behavior of small molecules were undertaken by Hefferlin and co-workers, resulting in triatomic periodic systems. 38 Geerlings and co-workers 39 (this paper is part of a festschrift in honor of professor Paul Geerlings) extended the early work of Parr et al 40 giving sharp definitions for well-known chemical concepts, allowing the calculation of important properties such as electronegativity and electronic polarizability in the framework of density functional theory (DFT). DFT is also known to predict molecular geometries accurately.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In 1985, Andreoni et al showed that a structural classification of molecules and clusters from valence electron orbital radii is possible, stressing the importance of the central atom. Broader efforts to search for periodic laws for the behavior of small molecules were undertaken by Hefferlin and co-workers, resulting in triatomic periodic systems . Geerlings and co-workers (this paper is part of a festschrift in honor of professor Paul Geerlings) extended the early work of Parr et al giving sharp definitions for well-known chemical concepts, allowing the calculation of important properties such as electronegativity and electronic polarizability in the framework of density functional theory (DFT).…”
Section: Introductionmentioning
confidence: 99%